2018
DOI: 10.3892/ijmm.2018.3671
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated 14‑3‑3β aggravates restenosis by promoting cell migration following vascular injury in diabetic rats with elevated levels of free fatty acids

Abstract: Mono‑unsaturated free fatty acids (FFAs) can serve as a predictive indicator of vascular restenosis following interventional therapy, particularly in individuals with high‑fat diet‑induced type 2 diabetes. However, the pathogenic mechanism remains to be fully elucidated. In the present study, the levels of tyrosine 3‑monooxygenase/tryptophan 5‑monooxygenase activation protein β (YWHAB; also known as 14‑3‑3β), in vascular smooth muscle cells (VSMCs) treated with different concentrations of oleic acid (OA) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Liu et al demonstrated that the activation of FXR in mice induced the activation of the AMPK-ACC-CPT1 pathway, a signaling pathway promoting fatty acid oxidation and achieving its lipid-lowering effect ( 8 ). Additionally, it has been established that in individuals with high-fat diet-induced type 2 diabetes, monounsaturated free fatty acids (FFAs) can serve as a predictive indicator of vascular restenosis following interventional therapy ( 9 ). Chronic diseases often occur when inflammation is persistent or has not been effectively resolved ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al demonstrated that the activation of FXR in mice induced the activation of the AMPK-ACC-CPT1 pathway, a signaling pathway promoting fatty acid oxidation and achieving its lipid-lowering effect ( 8 ). Additionally, it has been established that in individuals with high-fat diet-induced type 2 diabetes, monounsaturated free fatty acids (FFAs) can serve as a predictive indicator of vascular restenosis following interventional therapy ( 9 ). Chronic diseases often occur when inflammation is persistent or has not been effectively resolved ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, our prediction models showed that YHWAB could interact with of BH3-domain proteins, known to be related to apoptosis ( 52 ). YHWAB has been reported to bind to BAD, a BCL-2 associated agonist of cell death promoting apoptosis ( 53 ). Therefore, if YHWAB protein levels decrease due to epigenetic miRNA control in early RA subjects, apoptosis can be expected to be inhibited, an event reported in RA pathogenesis ( 51 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“… 18 Numerous genes or proteins act as important regulators of cellular processes in restenosis. 19 , 20 For instance, Feng et al 19 observed an increased 14-3-3 gene (YWHAB) in oleic acid–induced VSMCs and believed that the enhanced YWHAB may aggravate restenosis by promoting cell migration. Lv et al 20 found that Pin1 is upregulated in T2D mice (after wire-injury) tissues and in VSMCs isolated from the above mice, and the further cellular experiments demonstrated that Pin1 downregulation significantly promotes the apoptosis and inhibits metastasis of VSMCs.…”
Section: Discussionmentioning
confidence: 99%